Adult MTM1-related myopathy carriers: Classification based on deep phenotyping. (15th October 2019) - Cocanougher, Benjamin T.; Flynn, Lauren; Yun, Pomi; Jain, Minal; Waite, Melissa; Vasavada, Ruhi; Wittenbach, Jason D.; de Chastonay, Sabine; Chhibber, Sameer; Innes, A. Micheil; MacLaren, Linda; Mozaffar, Tahseen; et al.
Abstract : Objective: To better characterize adult myotubularin 1 ( MTM1 )–related myopathy carriers and recommend a phenotypic classification. Methods: This cohort study was performed at the NIH Clinical Center. Participants were required to carry a confirmed MTM1 mutation and were recruited via the Congenital Muscle Disease International Registry (n = 8), a traveling local clinic of the Neuromuscular and Neurogenetic Disorders of Childhood Section, National Institute of Neurological Disorders and Stroke, NIH and Cure CMD (n = 1), and direct physician referral (n = 1). Neuromuscular examinations, muscle MRI, dynamic breathing MRI, cardiac MRI, pulmonary function tests (PFTs), physical therapy assessments including the Motor Function Measure 32 (MFM-32) scale, and X chromosome inactivation (XCI) studies were performed. Results: Phenotypic categories were proposed based on ambulatory status and muscle weakness. Carriers were categorized as severe (nonambulatory; n = 1), moderate (minimal independent ambulation/assisted ambulation; n = 3), mild (independent ambulation but with evidence of muscle weakness; n = 4), and nonmanifesting (no evidence of muscle weakness; n = 2). Carriers with more severe muscle weakness exhibited greater degrees of respiratory insufficiency and abnormal signal on muscle imaging. Skeletal asymmetries were evident in both manifesting and nonmanifesting carriers. Skewed XCI did not explain phenotypic severity. Conclusion: This work illustrates the phenotypic range of MTM1 -related myopathy carriers in adulthood and recommends a phenotypic classification. This classification, defined by ambulatory status and muscle weakness, is supported by muscle MRI, PFT, and MFM-32 scale composite score findings, which may serve as markers of disease progression and outcome measures in future gene therapy or other clinical trials.